Projective Psychological Tests from the Point of View of Neural Network Theory of Society - Ibragim, Suleimenov; Mariya, Kostsova; Yelizaveta, Vitulyova (Journal of Ecohumanism, 2024)
It is shown that the issues raised by the international expert community in the discussion regarding the legality of using projective techniques (in particular, tests such as the Luscher test, the Szondi test and the Dellinger test) can be resolved on the basis of an adequate interpretation of the concept of “archetype” and an analogy with neural networks. At the same time, the interpretation of the concept “archetype” is based on the neural network theory of society, which allows us to remove the difficulties that arise with the traditional interpretation of this concept. It is shown that there is an equivalent scheme for the testing procedure, in which the testing itself can be reduced to the functioning of the external (output) layer of the general neural network, which also includes a neural network formed by the human brain. This approach makes it possible to remove many of the criticisms put forward against the use of projective techniques (even declaring them pseudoscientific), but it implies a significant change in existing approaches to the interpretation of results obtained when using tests of the type in question. Namely, within the framework of the proposed approach, not every possible combination of images on which the test is built makes sense. Such a meaning can be given only to some of them, specifically to those that are most often encountered in experiments. Such combinations, which can be interpreted as basic, are interpreted on the basis of an analogy with images recognized by a neural network. The remaining combinations are treated as images containing errors; they are reduced to the basic ones based on an analogy with the methods used in constructing error-resistant codes.